Gambaran Status Gizi Lansia di UPTD Puskesmas Pante Ceureumen - Laila Apriani Hasanah Harahap (Jurnal Sains dan Kesehatan, 2022)
The elderly are an age group that is vulnerable to nutrient digestion due to physiological, psychological, and social changes. This study aims to determine the nutritional status of the elderly in Krueng Bekah Village in the Pante Ceureumen Health Center work area. The method used is quantitative descriptive with a total sampling technique. Data collection was carried out by interviewing and anthropometric measurements. The results of this study showed that 68% of the elderly experienced malnutrition, 13% normal nutrition, and 19% overnutrition. The conclusion of this study is that the elderly mostly have poor nutritional status. The research suggestion is that the health center conducts anthropometric measurements and records the health status of the elderly comprehensively on the Healthy Menu Card for the elderly and counseling with nutrition experts regarding the health of the elderly to overcome these problems.